5x+11=5x-5

Simple and best practice solution for 5x+11=5x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+11=5x-5 equation:


Simplifying
5x + 11 = 5x + -5

Reorder the terms:
11 + 5x = 5x + -5

Reorder the terms:
11 + 5x = -5 + 5x

Add '-5x' to each side of the equation.
11 + 5x + -5x = -5 + 5x + -5x

Combine like terms: 5x + -5x = 0
11 + 0 = -5 + 5x + -5x
11 = -5 + 5x + -5x

Combine like terms: 5x + -5x = 0
11 = -5 + 0
11 = -5

Solving
11 = -5

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 16+8y=48 | | -1+2-(-3)=10 | | -4j=39 | | -34-5x=-12x+64 | | A+2=12 | | 4x+8+2x+3=51 | | -4(x-1)+2x=34+3x | | 7b^2+-14b+7=0 | | -3x-86=-9x+82 | | -7k-2k= | | -6-z=12 | | (4x^2+2)-(2x^2+3)= | | 11x-61=6x+89 | | X^2+4x=44 | | 4(y-4)-8y=20 | | 3(1-7n)= | | r-10=-12 | | x^2+3x=-4(-2x+1)-2 | | 12x-33=3x+75 | | -4.9x^2+9x+1.2=0 | | 2(2y-3)+3x=7 | | 0=2(2x^2-103x+546) | | 4x=x+5+2x-1 | | 4(j+5)=2 | | 13-2=j+6 | | -4(4a-8)= | | -4(4a-7)= | | Y=-12e^2x+36e^4x | | r+0.48=1.6 | | h(t)=-16x^2+85 | | 6(1)-(-7)=13 | | c/3+7=11/2 |

Equations solver categories